Von den Besiegten lernen?. Die kriegsgeschichtliche Kooperation der U.S. Armee und der ehemaligen Wehrmachtselite 1945-1961 - Howell, Esther-Julia 1981- (Studien zur Zeitgeschichte, 2016)
From 1945 to 1961, former Wehrmacht officers undertook thousands of historical studies on behalf of the US army. Shared points of view with the Americans and the advent of the Cold War enabled the German soldiers to develop a self-justifying interpretation of history that denied the German war of extermination. The Historical Division actively contributed to the transatlantic dissemination of this myth of the clean Wehrmacht